Aprovechamiento de los pétalos de rosa como mermas para la obtención de aceite esencial en la empresa MIDI FLOWERS - Luna Pazmiño, Víctor Andrés (2023)
The Ecuadorian floriculture industry experiences a significant decrease in sales to the foreign market during certain times of the year, resulting in losses for producers who discard or allocate the flowers for organic fertilizer. To make use of the waste produced by the floriculture industry, essential oil was extracted from rose petals. This forms the starting point of the research, aiming to add value to this product, regarding the floral company MIDI FLOWERS. As a first step in the project, a field investigation was conducted at the company from week 49 of 2021 to week 5 of 2022, analyzing 144,625 harvested roses against a total of 454 discarded stems. A sample was taken to the laboratory for essential oil extraction, employing hydro distillation and Soxhlet extraction. The data obtained from the farm were subjected to ANOVA analysis and tests for normality, homoscedasticity, and independence to determine the main reason for rose waste. In addition, calculations were conducted to determine the yield of each sample studied, and an ANOVA analysis was performed to determine the most efficient method. The obtained essential oil underwent organoleptic characterization, reflecting a characteristic rose scent with an opaque lilac color that turned yellow within a week, presenting a liquid appearance. The most effective method was found to be Soxhlet extraction. In the hydro distillation process, apart from the essential oil, rose water was obtained, which was characterized through physicochemical analysis. The results showed a pH range of 6.03 to 6.09, an acidity of 0.12% (citric acid), and a positive presence of flavonoids, quinones, and phenols. Finally, essential oil and rose water were obtained by utilizing rose waste, although the yield was lower compared to other studies.